Economic Impacts Of Port Development On Coastal Communities: A Vocational Education Perspective - Titis Ari Wibowo; Muhammad Zilal Hamzah; Eleonora Sofilda (International Journal of Economics, Management and Accounting, 2024)
This research investigates the economic impacts of port development and management on coastal communities, focusing on the role of vocational education in workforce preparation. Ports serve as pivotal economic hubs, driving regional growth through trade facilitation, job creation, and infrastructure development. However, they also pose environmental challenges such as pollution and habitat degradation, necessitating sustainable management practices. The study evaluates these dual aspects by analysing indicators such as GDP growth, workforce readiness, environmental sustainability, and strategic management in port operations. Findings highlight the significant contributions of ports to local economies while emphasising the importance of vocational education in equipping communities with skills for port-related jobs. Strategic management and governance are critical in maximising economic benefits while mitigating environmental impacts and ensuring regulatory compliance. The research underscores the need for integrated approaches that balance economic growth with environmental sustainability to foster resilience in coastal regions.